Dynamics of ultrathin films in the glassy state - Xavier, J H (Langmuir : the ACS journal of surfaces and colloids, 2005)
We report hole growth experiments in free-standing polystyrene (PS) films at temperatures up to 10 degrees C below the bulk glass transition. The data show an unexpected result: the growth rate of nucleated holes increases with increasing molecular weight, up to a limiting value beyond which the rate is approximately constant. Film thicknesses of 45, 80, and 100 nm were studied, using PS molecular weights ranging from 65K to 11.4 Mg/mol. Hole diameters grew linearly with time, and no growing rims were observed to form around the developing holes. Possible explanations in terms of elasticity, yield, and influence of sample preparation and confinement effects are discussed